Developing Islamic Housing Index based on Maqasid Approach - Zulfan, Ahmad; Taufiq, Muhammad; Ashraf, Gigih; Rizky, Muhamad Arul (SMART Insight, 2023)
Housing with Islamic concepts is starting to grow rapidly at this time. It is not uncommon for Islamic housing to be interpreted with the concept of housing without usury transactions, even though the concept includes six aspects of Maqasid Shariah, namely protecting religion, protecting the soul, protecting the mind, protecting offspring, protecting property, and protecting the environment. Therefore, this research aims to analyze the existing housing in Sentul, such as Azzikra, Griya Asri, and Victoria housing in Bogor Indonesia, on the basis of Maqasid Shariah. Using a quantitative approach and simple addictive research method, we found that in general indicators, all housing estates have conducted Islamic housing development in accordance with Maqasid Shariah. However, in this study we found that the housing that in overall indicators is almost close to fulfilling the Maqasid Shariah criteria is Victoria housing. In the future, this index is expected to become an alternative indexation for sharia-based housing.